Circulating Rare Cells: Nanostructured Substrates for Detection and Characterization of Circulating Rare Cells: From Materials Research to Clinical Applications (Adv. Mater. 1/2020). Issue 1 (7th January 2020) - Dong, Jiantong; Chen, Jie‐Fu; Smalley, Matthew; Zhao, Meiping; Ke, Zunfu; Zhu, Yazhen; Tseng, Hsian‐Rong
Abstract : Circulating rare cells are of great significance as a surrogate tissue source for implementing noninvasive diagnoses. In article number 1903663, Zunfu Ke, Yazhen Zhu, Hsian‐Rong Tseng, and co‐workers summarize the recent progress in exploring the use of nanostructured substrates to detect and characterize circulating tumor cells and circulating fetal nucleated cells. Different nanostructures, cell‐retrieval strategies, clinical applications, and future perspectives are comprehensively discussed.